Звезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активна
 
\begin{equation} 1){y}'=6x^{5}e^{x}+x^{6}e^{x}=x^{5}e^{x}(6+x); \end{equation} \begin{equation} 2){y}'=e^{x}\cos x+e^{x}(-\sin x)= \end{equation} \begin{equation} =e^{x}(\cos x - \sin x); \end{equation} \begin{equation} 3){y}'={(\frac{x+1}{e^{x}})}'= \end{equation} \begin{equation} =\frac{{(x+1)}'e^{x}-(x+1)*{(e^{x})}'}{e^{2x}}= \end{equation} \begin{equation} =\frac{e^{x}-(x+1)e^{x}}{e^{2x}}=\frac{e^{x}-e^{x}x-e^{x}}{e^{2x}}= \end{equation} \begin{equation} =\frac{e^{x}x}{e^{2x}}=-\frac{x}{e^{x}}; \end{equation} \begin{equation} 4){y}'={(6^{x})}'=6^{x}\ln 6; \end{equation}